Along‐wind response control of chimneys with distributed multiple tuned mass dampers. Issue 1 (23rd October 2018) - Elias, Said; Matsagar, Vasant; Datta, Tushar Kanti
Summary: The effectiveness of distributed multiple tuned mass dampers (d‐MTMDs) for multimode control of chimney for along‐wind response is presented. A concrete chimney considered herein is an assemblage of two‐dimensional (2D) beam elements, each assumed to have constant diameter over the element length. Along‐wind forces are simulated using the Kaimal wind spectrum. The response of the chimney is to be controlled by installing tuned mass dampers (TMDs). Suitable locations of the TMDs are identified along height of the chimney based on its uncontrolled (NC) mode shapes. A TMD unit is placed where the mode shape amplitude of the chimney is the largest or larger in a particular mode to be controlled and is tuned with the corresponding modal frequency—the approach is called multimode vibration response control. The number of modes to be controlled is decided according to desired total modal mass participation. The coupled differential equations of motion for the system are derived and solved using Newmark's step‐by‐step iteration method. The displacement and acceleration responses of the chimney under the along‐wind forces are computed to study the effectiveness of the d‐MTMDs as compared with single tuned mass damper (STMD) and with arbitrarily installed d‐MTMDs (ad‐MTMDs). In addition, suitable mass and damping ratios for the STMD, ad‐MTMDs, and d‐MTMDs are obtained to achieve improved dynamic response control. It is observed that the d‐MTMDs are effective controllers being designed as per vibration mode to be controlled.